2015
DOI: 10.1186/s12936-015-0823-z
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-6-phosphate dehydrogenase deficiency among malaria patients of Honduras: a descriptive study of archival blood samples

Abstract: Background:The frequency of deficient variants of glucose-6-phosphate dehydrogenase (G6PDd) is particularly high in areas where malaria is endemic. The administration of antirelapse drugs, such as primaquine, has the potential to trigger an oxidative event in G6PD-deficient individuals. According to Honduras´ national scheme, malaria treatment requires the administration of chloroquine and primaquine for both Plasmodium vivax and Plasmodium falciparum infections. The present study aimed at investigating for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…Two mutations were detected in most (71 %) of subjects with biochemically determined deficiency, particularly the 202G → A and the 376A → G, defining together the variant G6PD A- 202A/376G , widely distributed in Africa where it seems to confer resistance to falciparum malaria [ 19 , 36 ], and identified under other names in Spain, Mexico, Italy, and many other parts of the world [ 12 , 37 ]. High prevalence of this G6PD variant has been reported in Brazil, Mexico, Cuba and Honduras [ 20 – 22 , 38 ], but a great diversity of variants has been described and spread across American, European and Asian countries [ 12 , 19 , 23 ]. Although in this study four regions were studied spanning five exons of the G6PD gene, which include the most common mutations described in G6PDd subjects of LA countries, it is not possible to exclude those mutations located in other gene regions which can be involved in the deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Two mutations were detected in most (71 %) of subjects with biochemically determined deficiency, particularly the 202G → A and the 376A → G, defining together the variant G6PD A- 202A/376G , widely distributed in Africa where it seems to confer resistance to falciparum malaria [ 19 , 36 ], and identified under other names in Spain, Mexico, Italy, and many other parts of the world [ 12 , 37 ]. High prevalence of this G6PD variant has been reported in Brazil, Mexico, Cuba and Honduras [ 20 – 22 , 38 ], but a great diversity of variants has been described and spread across American, European and Asian countries [ 12 , 19 , 23 ]. Although in this study four regions were studied spanning five exons of the G6PD gene, which include the most common mutations described in G6PDd subjects of LA countries, it is not possible to exclude those mutations located in other gene regions which can be involved in the deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in malarious regions of the world, the prevalence rate of G6PD deficiency was reported to be 8% on average [25] which is lower than that (12%) in the present study. Nevertheless, the prevalence rate of the current report is lower than that of some parts of the world including Zuniga in Honduran (16.8%) [26] and is higher than that of some other areas such as Venezuela (3.6%) [26,27]. Interestingly, rate of G6PD deficiency among study participants in southeast and north of Iran is considerably higher than that in south and central part of Iran [28,29].…”
Section: Discussionmentioning
confidence: 41%
“…Several epidemiological studies demonstrated that G6PD deficiency is mainly distributed in areas of the world where malaria was previously or is currently endemic [11,21,25,26,32,35]. Similarly, there is various geographic distribution of G6PD deficiency in the study regions with the highest prevalence rate observed in Chahbahar District as one of the previously malaria endemic areas in contrast to the lowest prevalence rate seen in Zahedan District as non-malaria endemic region, although low/high prevalence of G6PD deficiency in endemic/non-endemic part can be due to some factors such as immigration of healthy or malarious individuals and method of sampling.…”
Section: Discussionmentioning
confidence: 99%
“…Different prevalence of G6PDd has been reported in Africa (20 %), the Mediterranean (4–30 %) and Southeast Asia (10–20 %) [ 11 ]. In Latin America, where it has been less studied, prevalence ranges from <2 % in countries such as Guatemala, Mexico and Peru to 16 % in Honduras [ 2 , 12 ], including Venezuela with a prevalence of ~4 % [ 13 ]. The G6PDd African variants or “A” variants are among the most frequent worldwide, and the most common variants reported in the Americas.…”
Section: Introductionmentioning
confidence: 99%